Smart Dc to DC converter for a Small Drone Based upon Deep Learning Technique - Al-bahrany, Mays Abbas; Sadda, Ahmad T. Abdul (Journal of Fuzzy Systems and Control, 2023)
Flying a small robot like a drone needs more conservative energy, small solar cell size needs to robust efficient DC-to-DC converter. Mathematical analysis for finding the optimal duty cycle in the PWM (pulse width modulation) is presented at different supplies voltage, considering a low voltage of 8 volts for low-speed motor rotation speed and 18 volts for high speed of the rotation motor. The dc-dc converter gets the power desired from the small robotic by using a dc-dc buck-boost converter with (PID control, smart tuning different rules fuzzy logic control, and a hybrid fuzzy-PID controller as one solution to be improved the controller to be capable on process any disturbances on the inductor or the desired value of the output voltage of the dc-dc converter